Heteroatoms binary-doped hierarchical porous g-C3N4 nanobelts for remarkably enhanced visible-light-driven hydrogen evolution - Wu, Jiaojiao; Li, Nan; Zhang, Xiao-Hong; Fang, Hua-Bin; Zheng, Yan-Zhen; Tao, Xia (Applied catalysis. B, Environmental, 2018)
[Display omitted] •C, O binary-doped hierarchical porous g-C3N4 nanobelts are fabricated.•Hierarchical porous structure with open-up surface largely enhances surface area.•C, O heteroatoms are introduced into the g-C3N4 texture by substituting N atoms.•C-O/CN shows enhanced visible-light harvesting and reducibility of electrons.•C-O/CN exhibits remarkable visible light photocatalytic H2 production activity. The heteroatoms C, O binary-doped g-C3N4 (C-O/CN) with hierarchical porous nanobelt architecture was synthesized via a straightforward template-free self-assembly method using dicyandiamide as g-C3N4 precursor and glutathione as C, O doping source. The as-prepared C-O/CN exhibits well-defined hierarchical nanobelt structure composed of porous nanosheets, resulting in obvious enhanced specific surface area (120 m2 g−1). Particularly, C, O heteroatoms, introduced into the structure of g-C3N4 by substituting N atoms, induce narrowed bandgap for more effective visible-light harvesting and negatively shifted conduction band position for stronger reducibility of electrons for H2 production. Such hierarchical porous C-O/CN nanobelts are demonstrated to be highly efficient in charge separation and transfer. Under optimal mass ratio of glutathione to dicyandiamide (0.1%), C-O/CN-0.1 shows a highest H2 evolution rate of 18.38 mmol h−1 g−1 under visible-light (λ > 420 nm) irradiation (about 79.9 times higher than that of the bulk g-C3N4) and a remarkable apparent quantum efficiency of 9.83% at 420 nm, which can be used as a promising low-cost photocatalyst for H2 evolution.